Einige Bemerkungen bey Betrachtung des Handatlas über alle bekannten Länder des Erdbodens, Herausgegeben von Herrn Professor Heusinger im Herbst 1809 - Ritter, Carl (ERDKUNDE, 1959)
Some remarks arising from the perusal of the 'Handatlas über alle bekannten Länder des Erdbodens' edited by Heusinger in 1801. This paper by CARL RITTER has been completely ignored in methodological writings, since it was erroneously held to be a mere review of the HEUSINGER atlas. In fact, however, RITTER had taken this atlas only as an occasion for stating his own views about geography, which differed greatly not only from the views held by HEUSINGER, but also from those generally held in his days. Until RITTER geography had been considered a field of knowledge that derived its value and necessity from its applicability: Thus it was either an ancillary subject of other fields, for instance history, or it was an accumulation of accidental and incoherent facts that were necessary for the educated person to move in society, or for the practical man to conduct his business more effeciently. RITTER opposes this concept of geography, and developes his own idea of the 'dignity' of geography as an independent science: The earth's surface is a phenomenon of nature, which shows, as a whole as well as in its parts, an inherent necessity, not an accidental origin. Just as the biologist investigates without bias the structure of a living being, and demonstrates its purposefulness, thus the geographer has to investigate the earth's surface. The intricacy of the facts and relations discovered will be great, and their relevation will take up many years of intense study. First of all the relief of the earth has to be disclosed, for it is important for the understanding of climate, as well as of many questions arising in biogeography and historical geography. This insight, however, is still obscured by the concept of'pure' geography that divides the earth into'dry' and 'wet' zones, and thinks in terms of a symmetrical arrangement of the continents. This apriorism has to be dropped, for it is not rooted in nature but in human reasoning; it is erroneous, and therefore does not bring us any further. Worth our attention is only a science that has an object of its own, and is endowed with necessity and legitimacy. RITTER'S theory of geography as an independent science was induced by PESTALOZZI, whose ideas he developed. To my kowledge this essay by RITTER is the first attempt of a methodological foundation of modern geography.